Pengaruh edukasi kesehatan tentang perawatan dan personal hygiene (mandi besar) dalam islam terhadap pengetahuan ibu nifas - Kirana Aulia Putri; Tyas Febriana; Arfan Syahroni (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Breast care is important to maintain hygiene, stimulate breast milk production, and prevent mastitis and abscesses. In addition, body hygiene and a major bath are also necessary to prevent postpartum infections and restore the mother's physical condition. This study aims to provide education on breast care and personal hygiene (major bath) in Islam to postpartum mothers. The success of health interventions can be seen from the decrease in MMR and IMR, where postpartum complications, especially in the breast, are often the cause of maternal death. Purpose: Improving postpartum mothers’ knowledge about personal hygiene (ritual bathing) and breast care in relation to health status. Methods: A total of 32 respondents participated in the study using a Quasi Experimental design with a pre-test and post-test methodology using one group. Paired T-tests were used for univariate and bivariate data analysis. Results: According to the results of the study, the majority of participants were quite knowledgeable about personal hygiene (65.5%) and breast care (59.4%) before receiving education. After education, the knowledge of postpartum mothers increased significantly, with 68.8% having knowledge good.about.maintenance.breast.and.81.3% on personal hygiene. Paired Tests show.mark..p=..0.001 (.p< 0.005.), Which..means..education has a significant influence.towards knowledge..Mother..postpartum... Conclusion:.Care education breast.and.personal..hygiene (major bath) can increase the knowledge of postpartum mothers, help overcome breast problems, support exclusive breastfeeding, prevent postpartum infections, and fulfill Islamic procedures for purification.